Faktor-Faktor Yang Mempengaruhi Partisipasi Anggota serta hubungannya dengan Keberhasilan Usaha Koperasi Wanita di Kabupaten Pasuruan - Diana, llfi Nur (ULUL ALBAB Jurnal Studi Islam, 2005)
The purpose of this research is to reveal the factors which affect member’s participation of Kopwan in Pasuruan. And to analyze the simultaneous and the partial influences of these factors. This reseach also to analyze influences members participation on the increasing business success. Hypotesis of this research are: (1) Social factors and economic factors affect positively the members participation of Kopwan, simultaneously or parsially. (2) Members participation affect positively the success bussiness of Kopwan in Pasuruan. The population of this research is five Kopwan in Pasuruan, and the respondens are 84 members of all of Kopwan. The hypotesis are tested by Path Analysis. The results of this res each are (1 ). Social factors) and economic factors affect positively the members participation of Kopwan, simultaneously or parsially. (2) Members participation affect positively the success bussiness of Kopwan in Pasuruan. Therefore Kopwan must care and increase members education, specially about cooperation, increase bussiness which fit the need members, give a fit price and rate of interest provitly. Managemen must do plan maximally and optimally, and collect obligatory saving on the agreed time with members of kopwan.